2013
DOI: 10.1111/jphp.12095
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of the human ether-a-go-go-related gene potassium channel by ketamine

Abstract: Ketamine blocks WT IhERG expressed in Xenopus oocytes in a concentration-dependent manner and predominantly interacts with the open hERG channels. The interaction of ketamine with hERG channel may involve the aromatic residues Tyr652 and Phe656.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…Furthermore, the IC 50 for these drugs (Kamiya et al., ) were much lower than the IC 50 for TMS established in our experiments. Ketamine, a partially reversible, open‐state voltage‐dependent K v 11.1 blocker showed also blocking activity at lower concentrations (Zhang et al., ) than those found for TMS or TRIM in our study. Therefore, TRIM and TMS might be considered moderate K v 11.1 blockers with fast recovery, suggesting binding to the closed state.…”
Section: Discussionsupporting
confidence: 49%
“…Furthermore, the IC 50 for these drugs (Kamiya et al., ) were much lower than the IC 50 for TMS established in our experiments. Ketamine, a partially reversible, open‐state voltage‐dependent K v 11.1 blocker showed also blocking activity at lower concentrations (Zhang et al., ) than those found for TMS or TRIM in our study. Therefore, TRIM and TMS might be considered moderate K v 11.1 blockers with fast recovery, suggesting binding to the closed state.…”
Section: Discussionsupporting
confidence: 49%
“…Ketamine has been reported to inhibit various ionic currents [29][30][31][32][33][34][35][36][37][38] . Hara et al reported that ketamine (30, 100, 300 μmol/L) dose-dependently blocked peak I Na in guinea pig ventricular myocytes [32] .…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that ketamine may have cardioprotective effects, but the underlying mechanisms are still unknown. Ketamine has been reported to inhibit various ionic currents, including the L-type Ca 2+ current (I CaL ) [29][30][31][32][33][34] , peak sodium current (I Na ) [32] , inward rectifier K + current (I K1 ) [30,35] , delayed rectifier K + current (I K ) [30] , ATP-sensitive K + current (I KATP ) [36,37] , and human ether-a-go-go-related gene (hERG) channel [38] . However, there is no study regarding the effects of ketamine on I NaL .…”
Section: Introductionmentioning
confidence: 99%
“… 9 The inhibitory effects on cardiac hERG channels have already been observed for other anesthetics, eg, ketamine (IC 50 =12.05±1.38 μM) and articaine (IC 50 =224±6 μM). 36 38 However, the inhibitory effects of midazolam on heterologously expressed hERG channels have not previously been described.…”
Section: Discussionmentioning
confidence: 99%